The Effect PjBL Model Based on STEAM and TPACK with Pakan Penyu Media on Mathematics Learning Outcomes - Hidayati, Siti Nur (Lembaga Pendidikan Hikmatun Najah Blora, 2022)
This study aims to determine whether there is an effect of the PjBL model based on TPACK and STEAM with Pakan Penyu media on mathematics learning outcomes. This study uses an experimental research design One Sample t Test. The analysis used is descriptive statistics. The population used were students of SDN Gembong 02 with a sample of grade 2 students. The results of the Test of Normality output, obtained the Shapiro-Wilk Sig value of 0.109 > 0.05 so the data is normally distributed. Table One Sample t Test obtained Sig value. (2-tailed) 0.000 < 0.05, the output of the One Sample t Test table shows that the t count value 35,446 > t table 2,060, then H0 rejected and Ha accepted. So it can be concluded that there is an effect of PjBL model based on STEAM and TPACK with Pakan Penyu media on mathematics learning outcomes.